Police ethics: crisis in law enforcement - Barker, Tom, Ph. D (Chares C. Thomas, 2011)
"This third edition has been comprehensively revised, expanding the information in the previous edition on the long-standing challenge of implementing effective, responsible, and acceptable practices in ethical police work. The author's unique perspective provides insights not found elsewhere and presents them in an informative, fact-filled, and encouraging way. The text is based on the premise that ethical crisis has always existed in law enforcement and stresses that policing is and always has been a 'morally dangerous occupation.' The moral dangers of policing are discussed in detail and emphasize how crucial ethical standards are for police officers. Four critical and primary questions addressed in the text are: Is law enforcement a profession? Can law enforcement officers be professional? What forms of behavior are the major law enforcement ethical violations? Can police ethical violations be controlled? Several chapters also thoroughly review the Law Enforcement Code of Ethics and include very up-to-date examples of notable violations by individual officers and police departments. Additional topics include major police corruption issues, including corrupt practices and corruption control; abuse of authority; and getting effective control of unethical behavior. The goal of this timely new edition is to provide officers, law enforcement managers, and city administrators with only the most current information, tools, and skills in identifying and dealing with unethical police behavior. It is valuable to both new and seasoned officers in a significant effort to make policing a true profession that is real and not rhetoric"--Provided by publisher